Does menopausal status influence rejection rate of polypropylene meshes used in urogynaecology? - Jankiewicz, Katarzyna; Adamiak, Aneta; Miotła, Paweł; Bogusiewicz, Michał; Wróbel, Andrzej; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Stress urinary incontinence and pelvic organ prolapse are common disorders in postmenopausal women. Surgical management of these diseases using prosthetic materials is highly efficient but not free of complications. One complication specifically associated with use of prosthetic material is its erosion. The aim of the study was to assess whether menopausal status influences the rate of mesh erosion after urogynaecological surgery. Among 830 women who underwent surgical procedures with polypropylene mesh at the 2 nd Department of Gynaecology between January 2002 and September 2005 the rejection rate was 4.5%. Menopausal status was established in 210 patients by measurement of serum FSH and E 2 levels. The rate of mesh rejection did not differ between premenopausal and postmenopausal women. In conclusion, menopausal status does not influence polypropylene mesh rejection rate after urogynaecological surgery